First Report of Mal de Rio Cuarto Virus and a Picorna-Like Virus Naturally Infecting Rice (Oryza sativa) in Argentina - Solis, Valentina Eva; Luciani, Cecilia Elizabeth; Brugo Carivali, María Florencia; Perotto, Maria Cecilia; Gutierrez, S.A.; Celli, Marcos Giovani (American Phytopathological Society, 2024)
Disease note / nota de enfermedad